Contact isolation versus standard precautions to decrease acquisition of extended-spectrum β-lactamase-producing Enterobacterales in non-critical care wards: a cluster-randomised crossover trial. Issue 5 (May 2020) - Maechler, Friederike; Schwab, Frank; Hansen, Sonja; Fankhauser, Carolina; Harbarth, Stephan; Huttner, Benedikt D; Diaz-Agero, Cristina; Lopez, Nieves; Canton, Rafael; Ruiz-Garbajosa, Patricia; Blok, Hetty; Bonten, Marc J; et al.
Summary: Background: The effectiveness of contact isolation for decreasing the spread of extended-spectrum β-lactamase-producing Enterobacterales (ESBL-E) has been questioned. The aim of this study was to establish the benefits of contact isolation over standard precautions for reducing the incidence density of ESBL-E colonisation and infection in adult medical and surgical wards with an active surveillance culture programme. Methods: We did a cluster-randomised crossover trial in adult wards in four European university hospitals. Medical, surgical, or combined medical–surgical wards without critical care were randomised to continue standard precautions alone or implement contact isolation alongside standard precautions for 12 months, followed by a 1 month washout period and 12 months of the alternate strategy. Randomisation was done via a computer-generated sequence, with a block size of two consecutive wards. Only laboratory technicians and data analysts were masked to allocation. Patients were screened for ESBL-E carriage within 3 days of admission, once a week thereafter, and on discharge. The primary outcome was the incidence density of ESBL-E, defined as the acquisition rate per 1000 patient-days at risk at the ward level and assessed in the per-protocol population, which included all patients screened at least twice with a length of stay of more than 1 week for each intervention period. No specific safety measures were assessed given the minimal risk of adverse events. The trial is registered, ISRCTN57648070. Findings: We enrolled 20 wards from four hospitals in Germany (eight wards), the Netherlands (four wards), Spain (four wards), and Switzerland (four wards). Between Jan 6, 2014, and Aug 31, 2016, 38 357 patients were admitted to these wards. Among 15 184 patients with a length of stay of more than 1 week, 11 368 patients (75%) were screened at least twice. The incidence density of ward-acquired ESBL-E was 6·0 events per 1000 patient-days at risk (95% CI 5·4–6·7) during periods of contact isolation and 6·1 (5·5–6·7) during periods of standard precautions (p=0·9710). Multivariable analysis adjusted for length of stay, percentage of patients screened, and prevalence in first screening cultures yielded an incidence rate ratio of 0·99 (95% CI 0·80–1·22; p=0·9177) for care under contact isolation compared with standard precautions. Interpretation: Contact isolation showed no benefit when added to standard precautions for controlling the spread of ESBL-E on non-critical care wards with extensive surveillance screening. Funding: European Commission.